The introduction of new technologies for out-patient care for tuberculosis patients during the COVID-19 pandemic in the Republic of Sakha (Yakutia) - A. F. Kravchenko; E. S. Prokopiev; L. P. Yakovleva; A. M. Lukina; E. F. Luginova; N. S. Val (Туберкулез и болезни лёгких)
During the COVID-19 pandemic in the Russian Federation associated with restrictions and quarantine, in order to ensure the quality and availability of tuberculosis medical care to the population of the Republic of Sakha, it became necessary to improve and search for new organizational forms of out-patient care.The objective of the study: to analyze the use of new technologies in out-patient care for tuberculosis patients in the Republic of Sakha (Yakutia) during the COVID-19 pandemic.Result: Scientific Practical Phthisiology Center introduced the following information and digital technologies to ensure the availability and quality of medical services to the population of the republic during the COVID-19 pandemic: Cloud Polyclinic, Telemedical Consultations, Radiological Information System of APK ArchiMed , Video-Controlled Treatment at Home, and Hospital at Home.All technologies have demonstrated their efficacy for remote medical consultations and contacting patients online. Based on practical experience, these technologies provided the following: improvement of medical care provided to the population through consultations, maintaining good contact with the patient, monitoring patients' well-being, and drug in-take. They assured compliance with general federal and regional anti-epidemic recommendations to prevent the spread of the new coronavirus infection.